PENERAPAN PEMBELAJARAN JARAK JAUH MENGGUNAKAN MOODLE DI KOMPETENSI KEAHLIAN TEKNIK KENDARAAN RINGAN OTOMOTIF SMK NEGERI 2 YOGYAKARTA - Fikri Prastowo; Wardan Suyanto (Jurnal Pendidikan Vokasi Otomotif, 2022)
This study aims to describe the implementation of distance learning (PJJ) using Moodle in terms of learning planning, learning process, and learning evaluation in KK TKRO SMK Negeri 2 Yogyakarta. This research is a type of qualitative descriptive research. The research subjects were 12 teachers. Data were collected by interview, observation, and documentation. Data analysis used descriptive analysis through data collection, data reduction, data presentation, and drawing conclusions. The results: (1) Planning of PJJ at KK TKRO SMK N 2 Yogyakarta is KD theory is taught all online with the main media Moodle, KD practice is taught 25% through face-to-face, lesson plans are containing identity, learning objectives, learning steps, and evaluation learning, the teaching materials are in the form of PPT, e-books, and videos; (2) The PJJ process at KK TKRO SMK N 2 Yogyakarta uses the assignment method with Moodle assisted by WhatsApp. The teacher uploads the material in Moodle then the students download and understand the material independently and then do the assignment; (3) Evaluation of PJJ in KK TKRO SMK N 2 Yogyakarta consists of knowledge evaluation using multiple choice tests, follow-up remedial for those who have not passed the KKM, skills evaluation is not carried out, attitude evaluation is carried out using observation techniques, follow-up for those whose attitudes are bad in the form of warnings, summons, or visit to student’s home.